Moderasi Relasi Lintas Agama Tau Samawa (Orang Sumbawa) Berbasis Keseharian di Tana Sumbawa - Yaspis Edgar Funay (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
This paper will analyze the interfaith relations based on people’s daily life patterns in Tana Sumbawa. Deeper, the author tries to see how a cultural-based lifestyle in society can also be one of the strengths and the closest way out to maintain community relations when they want to conflict or create post-conflict reconciliation. This paper draws a tentative conclusion that the original culture of the Sumbawa people can be a reconciliation of ideological conflicts and strengthen collective awareness because they have ethical values, morals, and good behavior as local products. Using a sociological perspective this paper examines the extent to which cultural values play a role in interfaith relations in Sumbawa. In the final part, this paper will explore the concept of Sumbawa culture as outlined in local philosophy as a concept of tolerance between religious communities in order to maintain the existence of the local cultural heritage.